American Indian Languages in the Eyes of 17th-Century French and British Missionaries - Kilarski, Marcin (Studia Anglica Posnaniensia, 2018)
This paper examines 17th-century descriptions of Algonquian and Iroquoian languages by French and British missionaries as well as their subsequent reinterpretations. Focusing on such representative studies as Paul Le Jeune’s (1592–1664) sketch of Montagnais, John Eliot’s (1604–1690) grammar of Massachusett, and the accounts of Huron by Jean de Brébeuf (1593–1649) and Gabriel Sagard-Théodat (c.1600–1650), I discuss their analysis of the sound systems, morphology, syntax, and lexicon. In addition, I examine the reception of early missionary accounts in European scholarship, focusing on the role they played in the shaping of the notion of ‘primitive’ languages and their speakers in the 18th and 19th centuries. I also discuss the impressionistic nature of evaluations of phonetic, lexical, and grammatical properties in terms of complexity and richness. Based on examples of the early accounts of the lexicon and structure of Algonquian and Iroquoian languages, I show that even though these accounts were preliminary in their character, they frequently provided detailed and insightful representations of unfamiliar languages. The reception and subsequent transmission of the linguistic examples they illustrated was however influenced by the changing theoretical and ideological context, resulting in interpretations that were often contradictory to those intended in the original descriptions.